PENERAPAN PSIKOEDUKASI SEKSUAL BERBASIS MEDIA TERINTEGRASI PEMBELAJARAN SEBAGAI UPAYA MENCEGAH KEKERASAN SEKSUAL SISWA SEKOLAH DASAR - Andriani, Opi; Nofrianni, Elvima; Pratiwi , Astriana (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The implementation of this community service is motivated by the role of teachers, which has not had an optimal impact in efforts to prevent sexual violence against elementary school students. Several things become obstacles in implementing sexual violence prevention, including teachers not being brave and taboo, teachers not understanding, and teachers not having educational and integrative strategies. One way to prevent violence against elementary school students is through media-based sexual psychoeducation that is integrated into learning. The Muara Bungo Muhammadiyah University service team conducted socialization on applying sexual psychoeducation to teachers at SD 196/II Taman Agung. Service activities use practical methods by means of simulations with direct assistance from the service team, which begins with material delivery. The series of activities were carried out in the meeting room and continued with the simulation in the classroom. The methods used during the service are lectures, discussions, simulations, and reflection. The result of implementing this service is that teachers gain a new understanding of the importance of sexual psychoeducation given from an early age; teachers can create and use media that contain elements of sexual psychoeducation according to the child's age and obtain strategies for applying appropriate language and tone according to the student's age so that learning with sexual psychoeducation content indeed leads to denotative.